Is current forest landscape research approaches providing the right insights? Observations from India context - Prasad, Rama Chandra P.; Rajan, Krishnan S. (Ecological Questions, 2015)
One of the major challenges in the current scenario for ecological conservation is to quantify the forest landscape in its spatio-temporal domain and understand further implications of those. While the detailed study of the forest ecosystems may provide insights into biodiversity, carrying capacity and productive nature, most of the studies are restricted to single time/event inventory and focused on assessment of tree diversity patterns. Through the adoption of geospatial technologies like remote sensing and Geographical Information System (GIS), though forest monitoring has been possible, the linkages to the biodiversity distribution and its patterns are still at an empirical level, thus supporting broad measures of protection and preservation without accounting for the local/regional variability. Towards this the paper discusses the lacuna in the current landscape research approaches in Indian scenario. Presents a framework to analyze the landscape structure at the, micro, meso and macro levels. Emphasize the need for the collection of spatio-temporal field data to analyze the change in biodiversity and their linked entities. The paper suggests the need for development of long term ecological area networks to understand the ecological processes, making the data open and improve collaborations among the organizations working in the similar domain to enhance the impact of the research works.